Changing Social Focussing in the Development of Jazz Music - Hay, James; Flynn, J David (Journal of Sociocybernetics, 2015)
This paper traces the development of jazz musical styles by relating those styles to the organization of jazz musicians and the social context of American society. The authors use a theory developed by Flynn and Hay (2012) derived from chaos and complexity science. The Flynn/Hay theory states that social focussing (chaos, complexity or order: SF) is directly proportional to internal structure (differentiation: D) and inversely related to external information (centrality: C). In mathematical terms: SF = D/C.The authors of this paper describe the social focussing of jazz styles in terms of being chaotic, complex or ordered. They then relate the styles of social focussing to the differentiation of the social system of jazz musicians, and the centrality inputs from the surrounding American society. Their results demonstrating that the style of jazz at each period from the late 19th century to the present era, is dependent upon the ratio of d/c.They conclude that the same analysis could be applied to subsystems of the jazz system, including the development of jazz styles in different geographic regions, as well as within each band and even over the career of each musician, in a kind of fractal effect, where the shape of social focussing is the same at each level.